Successful Use of Difelikefalin in Severe Chronic Kidney Disease–Associated Pruritus in a Patient With Complex Etiological Contributors: A Case Report - Johannes M. Werzowa; Margit Hemetsberger (Case Reports in Nephrology)
Conclusion: In a patient with longstanding conditions and multiple comorbidities, difelikefalin showed sustained effectiveness against H1-receptor antagonist– and gabapentin–resistant CKD-aP. Difelikefalin was well tolerated over the long term.